PRIORITAS STRATEGI KELEMBAGAAN PENGELOLAAN SUMBER DAYA IKAN LESTARI BERBASIS OTONOMI DAERAH DI KAWASAN SELAT BALI - S. Fauzi; B. H. Iskandar; B. Murdiyanto; E. S. Wiyono (Bogor Agricultural University, 2011)
This paper describes some prioritised strategies and its concept of implementation for institution related to capture fisheries resources in Bali Strait within local governance context in order to implement sustainable fiheries concept. Analysis Hierachy Process (AHP) was applied to construct the sequence of priorities. The results show that prioritised strategy, in sequence, were management development is carried out by specific institution that formed by local goverment (RK = 0,284), intensively coordination in local government to control fishing gear allocation and conflict (RK = 0,243), development of all management effort by each local government (RK = 0,216), development of intensively coordination of local government in each managemnent activities (RK = 0,148) and developmentof intensively of local government to control fishing gear allocation and fishing ground (RK = 0,109). Implementation concept of prioritised strategy (management development is carried out by specific institution that formed by local government) was the specific institution should play roles as an excecutor of fisheries resources conservation program, as a manager in fish resources utilization appropriate to SKB (catch quota, number of fishing gear, potential fishing ground), as a controller in selling price and fishing gears operation periodically, as an information centre of human resources in fisheries and its development and as a facilitator in development of local income generating contributed from fisheries sector.